Generation of epitope tag knock-in mice with CRISPR-Cas9 to study the function of endogenous proteins - Zhao Zhang (STAR Protocols, 2023)
Summary: Studying endogenous proteins in mice has provided numerous insights into the physiological and pathological roles of these proteins. However, the availability and specificity of protein-specific antibodies often limit such studies. Here we present a protocol for generating epitope tag knock-in mice with CRISPR-Cas9-mediated gene editing. We discuss key considerations for tag selection and knock-in location and provide insights into CRISPR design. Subsequently, we outline the sequential steps involved in knock-in mouse generation, genotyping, and validation and explore potential applications.For complete details on the use and execution of this protocol, please refer to Zhang et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.